A Green Emitting Organic Non-linear Optical Crystal (E)-4-Bromo-2-(((2-(2- hydroxyethoxy)ethyl)imino)methyl)phenol: Crystal Structure, Spectroscopic studies, Anticancer Activity - Priyanka. J; Ida Malarselvi. R; Vinitha. G; Ramachandra Raja. C; Priscilla. R (The Bioscan, 2026)
(E)-4-Bromo-2(((2-(2-hydroxyethoxy)ethyl)imino)methyl)phenol (E-4B2HMP), a unique series of solid crystal, with a laser-induced damage threshold (LIDT) and a notable non-linear optical coefficient.